Temperature-dependent dielectric anomalies in powder aerosol deposited ferroelectric ceramic films - Eckstein, Udo; Exner, Jörg; Bencan Golob, Andreja; Ziberna, Katarina; Drazic, Goran; Ursic, Hana; Wittkämper, Haiko; Papp, Christian; Kita, Jaroslaw; Moos, Ralf; Webber, Kyle Grant; Khansur, Neamul Hayet (Journal of Materiomics, 2022)
Room-temperature fabrication of functional ceramic films using powder aerosol deposition (AD) is important for practical applications. However, the as-processed ferroelectric films show unusual temperature-dependent dielectric response, including enhanced conductivity in the as-processed state and subsequent significant increase in the permittivity following heat treatment. In this work, we investigate the influence of the residual internal stresses developed during the high-impact consolidation process on the dielectric response. Moreover, the recombination of charged defects generated during deposition is driven by the temperature and the atmospheric condition during the heat treatment as well as the carrier gas type used during deposition. Thermal treatment up to 500 °C in different atmospheres was used to tune the dielectric and ferroelectric response, highlighting that irrespective of the type of carrier gas, AD deposition process induces charged defects in polar oxide ceramics that can be reduced through heat-treatment far-below their bulk sintering temperature. Macroscopic electromechanical properties are contrasted to in-situ heating scanning transmission electron microscopy to observe possible local effects, such as crystallization, grain growth, crystal defect structure, or grain reorientation. In addition X-ray diffraction and X-ray photoelectron spectroscopy studies were conducted to gain insight into the effect of annealing on the crystal structure and local moisture adsorption.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Aerosol deposition; Energy storage; Functional ceramic thick films; Structural characterization